16S Metagenomic Comparison of Plasmodium falciparum–Infected and Noninfected Anopheles gambiae and Anopheles funestus Microbiota from Senegal - Bassene, Hubert (Am J Trop Med Hyg, 2018)
In the context of the pre-elimination of malaria, biological control may provide an alternative or additional tool to current malaria control strategies. During their various stages of development, mosquitoes undergo subsequent changes in their associated microbiota, depending on their environment and nutritional status. Although Anopheles gambiae s.l. and Anopheles funestus are the two major malaria vectors in Senegal, the composition of their microbiota is not yet well known. In this study, we explored the microbiota of mosquitoes naturally infected or not by Plasmodium falciparum (Pf) using the 16S ribosomal RNA gene-based bacterial metagenomic approach. In both vector species, the microbiota was more diverse in Pf-infected samples than in the noninfected ones, although the total number of reads appeared to be higher in noninfected mosquitoes. Overall, the microbiota was different between the two vector species. Noteworthy, the bacterial microbiota was significantly different between Pf-positive and Pf-negative groups whatever the species, but was similar between individuals of the same infection status within a species. Overall, the phylum of Proteobacteria was the most predominant in both species, with bacteria of the genus Burkholderia outweighing the others in noninfected vectors. The presence of some specific bacterial species such as Asaia bogorensis, Enterobacter cloacae, Burkholderia fungorum, and Burkholderia cepacia was also observed in Pf-free samples only. These preliminary observations pave the way for further characterization of the mosquito microbiota to select promising bacterial candidates for potential use in an innovative approach to controlling malaria and overcoming the challenges to achieving a malaria-free world.